REGULASI WAKAF UANG DIGITAL PADA PLATFORM FINTECH SYARIAH DI INDONESIA: ANALISIS YURIDIS DAN KEKOSONGAN HUKUM - Muhammad Rafi Maulana (Universitas Nurul Jadid, 2026)
The rapid growth of Islamic fintech in Indonesia has propelled digital cash waqf collection from Rp61.2 billion in 2019 to Rp571.8 billion in 2024 (CAGR 56.4%), exposing a fundamental structural mismatch: Law No. 41 of 2004 on Waqf — the lex specialis — was designed for face-to-face transactions with no digital provisions, creating legal uncertainty as this study's central problem. This normative legal study employs statute, conceptual, and comparative approaches, applying a regulatory harmonization framework to map normative gaps across Law No. 41 of 2004, Government Regulation No. 42 of 2006, BWI Regulation No. 1 of 2020, UU ITE, and OJK fintech regulations, using Malaysian waqf instruments as reference. Three legal vacuums are identified: first, Article 17's physical presence requirement before PPAIW renders electronic waqf contracts legally uncertain, as UU ITE — lex generalis — cannot override the Waqf Law's lex specialis formality; second, no dedicated consumer protection exists for waqif funds on non-bank fintech platforms outside banking-grade deposit protection; and third, absent interoperability standards between national payment infrastructure (GPN/QRIS/BI-FAST) and digital waqf platforms produce data fragmentation impeding oversight. Comparative analysis shows proactive inter-institutional coordination between JAWHAR and Bank Negara Malaysia produces measurably superior outcomes in platform integration, fund security, and public trust. Grounded in maqasid al-shari'ah, closing these vacuums constitutes a substantive Islamic obligation rooted in hifzh al-mal and maslahah. Three normative recommendations: amendment of Article 17 of Law No. 41 of 2004 to recognize digital waqf; joint OJK-BWI regulation on fintech waqf; and a standardized Digital Waqf API Framework by Bank Indonesia.